Deteksi Gen Jamur Candida albicans pada Saliva Penderita Diabetes Melitus Dengan Metode Polymerase Chain Reaction - Sophia, Anggun; Suraini, Suraini; Arhesta, Silvi (LPPM UNIVERSITAS PERINTIS INDONESIA, 2024)
Diabetes mellitus is a predisposing factor that increases the risk of oral candidiasis, where the oral cavity of patients becomes an ideal environment for fungal growth due to excess glucose in saliva secretion. This glucose accumulation, along with disturbances in the salivary glands, can trigger the growth of Candida albicans, making it a significant health issue. To accurately detect the presence of Candida albicans, the Polymerase Chain Reaction (PCR) method is used, which allows for the identification of fungal genes with high sensitivity. The aim of this study is to detect the Candida albicans gene in the saliva of women with diabetes mellitus using the Polymerase Chain Reaction method. This research is an analytical study with a cross-sectional design. The samples used in this study are saliva from 10 diabetes mellitus patients experiencing oral pain symptoms. The examination procedures include saliva sample collection, fungal culture testing using Sabouraud Dextrose Agar (SDA), conventional identification, and fungal gene detection using the PCR method. This process includes fungal sample preparation, DNA extraction, DNA amplification, and agarose gel electrophoresis. The results show that 1 respondent tested positive for Candida albicans in the saliva sample, with a percentage of 10%, while 90% were negative. Positive test results were determined through macroscopic analysis of fungal cultures, microscopic examination with Gram staining, and further testing using the germ tube method. The positive sample was then analyzed for fungal gene detection using the PCR method with Internal Transcribed Spacer (ITS), where Candida albicans was detected in the ITS region with a product length of 600 bp.